STUDYING ETHNOGRAPHIC VOCABULARY IN THE UZBEK LANGUAGE - Xasanova, Kamila (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
Today in linguistics is gave a speciai attention to the study of vocabulary with national colours. In this article, we examined the use and study of ethnographic vocabulary in the Uzbek language, examples of scientific works of various linguists , and their distinctive features.